Decreased Proliferation in the Neurogenic Niche, Disorganized Neuroblast Migration, and Increased Oligodendrogenesis in Adult Netrin-5-Deficient Mice - Ikegaya, Shunsuke; Iga, Yurika; Mikawa, Sumiko; Zhou, Li; Abe, Manabu; Sakimura, Kenji; Sato, Kohji; Yamagishi, Satoru (Frontiers in Neuroscience, 2020)
In the adult mouse brain, neurogenesis occurs mainly in the ventricular-subventricular zone (V-SVZ) and the subgranular zone of the hippocampal dentate gyrus. Neuroblasts generated in the V-SVZ migrate to the olfactory bulb via the rostral migratory stream (RMS) in response to guidance molecules, such as netrin-1. We previously showed that the related netrin-5 (NTN5) is expressed in Mash1-positive transit-amplifying cells and doublecortin-positive neuroblasts in the granule cell layer of the olfactory bulb, the RMS, and the subgranular zone of the adult mouse brain. However, the precise role of NTN5 in adult neurogenesis has not been investigated. In this study, we show that proliferation in the neurogenic niche is impaired in NTN5 knockout mice. The number of proliferating (EdU-labeled) cells in NTN5 KO mice was significantly lower in the V-SVZ, whereas the number of Ki67-positive proliferating cells was unchanged, suggesting a longer cell cycle and decreased cell division in NTN5 KO mice. The number of EdU-labeled cells in the RMS and olfactory bulb was unchanged. By contrast, the numbers of EdU-labeled cells in the cortex, basal ganglia/lateral septal nucleus, and corpus callosum/anterior commissure were increased, which largely represented oligodendrocyte lineage cells. Lastly, we found that chain migration in the RMS of NTN5 KO mice was disorganized. These findings suggest that NTN5 may play important roles in promoting proliferation in the V-SVZ niche, organizing proper chain migration in the RMS, and suppressing oligodendrogenesis in the brain.